2020
DOI: 10.1177/1096348020944435
|View full text |Cite
|
Sign up to set email alerts
|

A Study On The Influencing Factors Of Tourism Demand From Mainland China To Hong Kong

Abstract: Tourism research increasingly uses search query data to forecast demand, but the literature rarely explores the mechanisms of the factors influencing demand. A time-varying parameter factor vector auto-regression model is constructed based on Baidu Index on six aspects (dining, shopping, transportation, tours, attractions, and lodging) of tourism demand from January 2011 to March 2019. The model can quantitatively and comprehensively analyze the mechanisms of tourism demand and its six important influencing fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 61 publications
1
10
0
Order By: Relevance
“…Results suggested a recovery of tourism arrivals of 10% to 70% compared to 2019 under different scenarios. Liu and colleagues (2021) developed a scenario-based judgmental forecast technology based on a novel index and found that the extent of recovery depended on the destination’s dependence on long-haul markets. Kourentzes and colleagues (2021) combined multiple forecasting methods to accomplish the tourism forecasting task in the first stage and conducted judgmental adjustment of model-based forecasting in the second stage.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Results suggested a recovery of tourism arrivals of 10% to 70% compared to 2019 under different scenarios. Liu and colleagues (2021) developed a scenario-based judgmental forecast technology based on a novel index and found that the extent of recovery depended on the destination’s dependence on long-haul markets. Kourentzes and colleagues (2021) combined multiple forecasting methods to accomplish the tourism forecasting task in the first stage and conducted judgmental adjustment of model-based forecasting in the second stage.…”
Section: Related Workmentioning
confidence: 99%
“…Specifically, with the development of the Internet and other information sources, tourists tend to collect information about a destination in advance, such as hotels, weather, and transportation. This behavior has triggered the rise and development of search engine data ( Liu, Liu et al, 2021 ). Owing to their real-time and high-frequency characteristics, search engine data are used in tourism demand forecasting to supplement traditional data sources and obtain a better grasp of the future trends in tourism ( Li & Law, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Wickramasinghe and Ratnasiri [ 5 ] used travel data classified by region and time and Google search data to improve the accuracy of travel forecasts in Sri Lanka during the COVID-19 pandemic. Liu et al [ 40 ] and Zhang et al [ 13 ] proposed scenario-based judgmental forecasting to analyze the amount of tourism recovery after the COVID-19 epidemic, respectively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Considering that the transportation system of most provincial tourism destinations includes both HSR and aviation, the examination of the combined effect of those two transportation infrastructures on tourism development is necessary and urgent. As a result of the COVID-19 pandemic, demand for international travel has dropped significantly [31]. Thus, domestic tourism demand has become an indispensable force in stimulating economic Land 2023, 12, 216 2 of 18 growth [32].…”
Section: Introductionmentioning
confidence: 99%